PENGARUH MODEL PEMBELAJARAN PROJECT-BASED LEARNING (PJBL) BERBASIS STEM TERHADAP KEMAMPUAN BERFIKIR KREATIF SISWA PADA MATERI IPA KELAS IV DI SDN 01 DEMANGAN - Berlian Diva Kartikasari; Raras Setyo; Naniek Kusumawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
There is a need for innovation in science learning that can facilitate and improve science process skills, especially understanding, skills, and the ability to make projects that produce products in order to hone students' creative thinking skills with the STEM-based PjBL model. The research was conducted to determine the effect of the STEM-based Project Based Learning (PJBL) learning model on the creative thinking skills of elementary school students. In this study using a type of quantitative research with pre-experimental design method type one group pre-test post-test design. The number of samples in this study were 20 students. The data collection techniques used in this study were observation, interviews, documentation, and tests. The results of this study indicate the influence of the STEM-based project-based learning model on the creative thinking skills of students on the material of Energy Transformation Topic Energy Changes, where the sig value. (2-tailed) 0.000 <0.05, so it can be concluded that there is a real difference in the creative thinking ability of students between before and after the implementation of the STEM-based project-based learning model.